단축형 청소년용 정신화 프로그램의 학생정신건강 증진효과 평가 - 오소영(So Young Oh); 문수진(Su Jin Moon); 이원혜(Won Hye Lee); 홍민하(Min Ha Hong); 민정원(Jung Won Min); 김봉석(Bong Seog Kim); 황준원(Jun Won Hwang); 우이혁(Ieehyok Woo); 반건호(Geon Ho Bahn) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2012)
Objectives : We developed the short form of the Mentalization Improvement Program for Adolescent-Community Model (MIPAdo-CM-S), based on the concept of the mentalization. Methods : The MIPAdo-CM was composed of 6 sessions and was applied to 133 students in the 1st grade of a middle school for six weeks during their regular school hours. After 6 weeks, we compared the endpoint changes of Adolescent Mental Problem Questionnaire-Revised (AMPQ-R), Emotional Empathy Test, Peer Aggression Scale, Peer Bullying Scale, School Adjustment Scale, Test Anxiety Inventory and Visual Analogue Scale between the subject and the control group. Results : On the Visual Analoge Scale, students in the trial classes reported an increased understanding and respect for others, as well as themselves. Conclusion : The efficacy of MIPAdo-CM was subjective improvement of understanding and respect for both others and themselves. To prove objective usefulness of this program, further studies should be administered in the form of long-term, regular and structured courses.